Enfermedades crónico degenerativas más frecuentes de los adultos mayores en los centros geriátricos de atención permanente y diurnos de la ciudad de Loja - Cárdenas Fernández, Hernán Andrés (2021)
The aging is a phenomenon present throughout the vital cycle from the same process of the conception until the death, for that reason in the present work a study of the chronic degenerative diseases but frequent in this group is made, dividing it thus in groups Older young, old, long-lived and centennial, which will allow us to have a greater information about certain specific types of pathologies that appear in the older adult in the city of Loja, and thus develop a comprehensive management in addition to strategies for prevention and promotion that should be the priority in public health, the sample was 100 older adults of which 60 met the criteria for the study, which were evaluated with a patient interview and review of medical records of all patients involved, the results show that the most common chronic degenerative diseases are 37.5% arterial hypertension, with 14.6% they share diabetes and sarcopenia, followed by physiological cognitive impairment with 7.6%, heart diseases such as peripheral arterial disease 1% and others 5.4%, these diseases all receive control and frequent medication in an adequate way to control and help a better quality of life. Chronic degenerative diseases in geriatric patients should be considered as an important health problem, so it is necessary to assess their risk in the population considered susceptible to plan a comprehensive care diagnosis and treatment. In addition to the family importance that has direct relation with the children that can develop the same disease of their parents, which with strategy would help to a better control and to diminish the risk of suffering it in a not very near future. Keywords: Aging chronic degenerative fiseases, fisiology Impairment, high blood pressure, sarcopenia, diabetes, comprehensive care.